2017
DOI: 10.1155/2017/2306458
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Security Mechanisms for Big Data in Health and New Alternatives for Hospitals

Abstract: Computer security is something that brings to mind the greatest developers and companies who wish to protect their data. Major steps forward are being taken via advances made in the security of technology. The main purpose of this paper is to provide a view of different mechanisms and algorithms used to ensure big data security and to theoretically put forward an improvement in the health-based environment using a proposed model as reference. A search was conducted for information from scientific databases as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As it has been previously introduced, a good number of systematic reviews can be found in the field of Big Data [18,27] and specific domains such as the health sector [17,18,31] the same manner, scientific programming techniques have been widely studied and reviewed [7,8]. However, the application of Big Data technology and scientific programming techniques to the engineering domain has not been fully reviewed, and it is not easy to draw a comprehensive picture of the current state of the art apart from works in specific domains such as climate [32] or astronomy [20].…”
Section: Review Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been previously introduced, a good number of systematic reviews can be found in the field of Big Data [18,27] and specific domains such as the health sector [17,18,31] the same manner, scientific programming techniques have been widely studied and reviewed [7,8]. However, the application of Big Data technology and scientific programming techniques to the engineering domain has not been fully reviewed, and it is not easy to draw a comprehensive picture of the current state of the art apart from works in specific domains such as climate [32] or astronomy [20].…”
Section: Review Protocolmentioning
confidence: 99%
“…Last years have also seen a large body of work in the field of Big Data covering from the creation of tools and architectural frameworks to its application to different domains [10][11][12] such as social network analysis [13], bioinformatics [14], earth science [15], e-government [16], e-health [17,18], or e-tourism [19]. More specifically, in the context of engineering and industry, some works have been reported [20] by large companies such as Teradata in particular domains such as maintenance of aircraft engines.…”
Section: Introductionmentioning
confidence: 99%
“…As Machine Learning (ML) is a technique consisting of a dataset that identifies relationships between features and algorithm outputs, it was applied in this study. By using algorithms, it is possible to develop techniques that allow the computer to "learn" to classify features, creating algorithms capable of generalizing data from unstructured information as samples [4,5]. Machine learning is very useful in the early diagnosis of affliction and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A supervised learning algorithm analyzes the input data (characteristics analyzed) and produces an output which is the variable being predicted [6,7]. By selecting the features, relationships and patterns can be established between the data and features about which we wish to make a prediction [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…A set of data can be used to identify links between algorithm attributes and outputs. Using feature selection, it is possible to establish links and patterns between data and the attribute about which one wishes to make the prediction [17,18]. There is a great variety of algorithms used in machine learning, some of which enjoy major popularity, namely, Nearest Neighbors, Linear SVM (Support Vector Machines), RBF (Radial Basis Function) SVM, Gaussian Process RBF, Decision Tree, Random Forest, AdaBoost, and Gaussian Naive Bayes.…”
Section: Introductionmentioning
confidence: 99%